Seni Pertunjukan Dalam Ibadah Ekspresif Di Gereja Sidang Jemaat Allah (GSJA) Lembah Pujian Kasongan - Cristi Devi Darnita (Indonesia Christian Religion Theologians Association and Widya Agape School of Theology, 2022)
Implementing Community Service Activities for the Religious Performing Arts Study Program in partnership with GSJA Lembah Pujian Kasongan. Partners' problem is that performing arts in expressive worship still needs to be optimal. Based on these problems, the PKM Team uses the Asset-Based Community-Driven Development (ABCD) method, which focuses on assets already owned by partners. The solution offered by considering the existence of assets and potential is to provide tambourine dance training and illustrations of God's words to improve performing arts in expressive worship at GSJA Lembah Pujian Kasongan. PKM activities are carried out in three stages, namely: 1.Pre-training, which includes surveys and observations; 2. Training which includes tambourine dance training and illustrations of God's word; and 3. Evaluation in the form of participants' performances at Sunday services and questionnaires related to the training given. The expected output of this training is that the participants understand the concept and apply the tambourine dance in service and the concept of illustrating God's word in the form of drama. Pelaksanaan Kegiatan Pengabdian Kepada Masyarakat Program Studi Seni Pertunjukan Keagamaan bermitra dengan GSJA Lembah Pujian Kasongan. Permasalahan yang dimiliki oleh mitra adalah belum optimalnya penggunaan seni pertunjukan dalam ibadah ekspresif. Berdasarkan permasalahan tersebut, Tim PKM menggunakan metode Asset Based Community-Driven Development (ABCD) yang berfokus pada aset yang telah dimiliki mitra. Solusi yang ditawarkan dengan melihat adanya aset dan potensi adalah dengan memberikan pelatihan tari tamborin dan ilustrasi firman Tuhan sebagai upaya peningkatan seni pertunjukan dalam ibadah ekspresif di GSJA Lembah Pujian Kasongan.Kegiatan PKM dilaksanakan melalui tiga tahap yaitu (1) pra pelatihan yang meliputi survei dan observasi, (2) pelatihan yang meliputi pelatihan tari tamborin dan ilustrasi firman Tuhan, dan (3) evaluasi dalam bentuk penampilan peserta pada ibadah hari Minggu dan kuisioner terkait pelatihan yang telah diberikan. Luaran yang diharapkan pada pelatihan ini adalah peserta memahami konsep dan mengaplikasikan tari tamborin dalam bentuk pelayanan dan konsep ilustrasi firman Tuhan dalam bentuk drama.